Pengelolaan Sumber Daya Alam Dalam Perspektif Islam - Rahmadani, Nur Fitri; M, Misbahuddin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Many people use natural resources excessively without thinking about the damage that will occur. This is due to a lack of public and government awareness in managing natural resources. In Islam, natural resources are a great gift from Allah SWT. which must be appreciated, cared for and managed well. The aim of this research is to provide insight into the management of natural resources from an Islamic perspective. The method used in this research is qualitative library research. The results of Islam have provided clear concepts in managing natural resources, such as the concept of ihyaul mawat or bringing life to dead land and al imar or prospering the surrounding nature. This concept is one of Islam's recommendations to be able to utilize natural resources as a requirement in Islamic teachings.